2020
DOI: 10.3389/fpsyg.2020.01491
|View full text |Cite|
|
Sign up to set email alerts
|

Psychological Symptoms During the Two Stages of Lockdown in Response to the COVID-19 Outbreak: An Investigation in a Sample of Citizens in Northern Spain

Abstract: Spain has been in a state of emergency since 14th March due to the COVID-19 crisis. This state of emergency means that the population must comply with strict rules such as lockdown (confinement to their homes except for essential trips) and social distancing. The aim of this study was to examine the psychological state of the general population in a sample recruited in Northern Spain. Sociodemographic and psychological data were gathered, assessing variables such as stress, anxiety, and depression. A questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

42
228
10
32

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(312 citation statements)
references
References 55 publications
42
228
10
32
Order By: Relevance
“…Lockdown conditions were associated with higher negative mood overall. This is compatible with previous research indicating that reduced, or the perception of reduced, social contact and health-based fears are related to poor wellbeing ( Bai et al, 2004 ; Hawryluck et al, 2004 ; Cacioppo and Hawkley, 2009 ; Chen and Feeley, 2014 ) as well as previous research on psychological effects of quarantine or lockdown conditions ( Brooks et al, 2020 ; Ozamiz-Etxebarria et al, 2020 ). Our results show that improvement in negative mood states were found quite quickly after the easing of lockdown conditions.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Lockdown conditions were associated with higher negative mood overall. This is compatible with previous research indicating that reduced, or the perception of reduced, social contact and health-based fears are related to poor wellbeing ( Bai et al, 2004 ; Hawryluck et al, 2004 ; Cacioppo and Hawkley, 2009 ; Chen and Feeley, 2014 ) as well as previous research on psychological effects of quarantine or lockdown conditions ( Brooks et al, 2020 ; Ozamiz-Etxebarria et al, 2020 ). Our results show that improvement in negative mood states were found quite quickly after the easing of lockdown conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Spending time in lockdown conditions has had a negative impact on mood, and this is in line with previously published work on the effects of COVID-19 lockdown on mental health ( Ozamiz-Etxebarria et al, 2020 ). These results add to the growing body of literature on health and wellbeing during and after the COVID-19 pandemic and demonstrates that changes to health behaviors during this time may be to come extent responsible for poorer mood, anxiety and depression.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings on the prevalence of depression, anxiety and stress among doctors were generally similar to the general population in other countries that implemented lockdown measures [ 39 , 40 , 41 , 42 ]. Physiologically, this could be due to the differences in exposure to sufficient sunlight during lockdown, which causes a fall in serotonin levels that is associated with emotional disorders such as anxiety and depression [ 40 , 43 ]. Psychologically, it could be due to sudden disruption in life routines, being frequently connected to the internet, avoiding activities due to peer pressure, or economic struggles [ 44 ].…”
Section: Discussionsupporting
confidence: 82%
“…In addition, the epidemic is also occurring against the backdrop of growing mental health issues in particularly vulnerable groups in Vietnam ( 21 ). Previous studies suggested that people with different social-economic backgrounds and history/risk of exposure to the COVID-19 experienced a different severity level of mental health problems ( 13 , 22 , 23 ). Therefore, this study aimed to identify the psychological impacts of COVID-19 on Vietnamese people under the first nationwide lockdown.…”
Section: Introductionmentioning
confidence: 99%